Male partners of subfertile couples in which the spouse is obese display adverse weight and lifestyle associated with reduced sperm quality. Issue 3 (May 2019) - Belan, M.; Carranza-Mamane, B.; Pesant, M.H.; AinMelk, Y.; Duval, K.; Jean-Denis, F.; Langlois, M.F.; Baillargeon, J.P.
Abstract: Objectives: To assess: 1—the spousal concordance of lifestyle and anthropometric characteristics between partners of infertile couples in which the woman is obese; and 2—in men, the influence of these characteristics on their conventional seminal parameters. Design: Cross-sectional study. Setting: Fertility clinic of the Centre hospitalier universitaire de Sherbrooke, Canada, between January 2012 and February 2015. Patients: 97 infertile heterosexual couples in which women were obese and seeking fertility treatments. Intervention: Not applicable. Main outcome measures: Weight and percentage of fat mass were evaluated using a scale with foot-to-foot bio-impedance. Abdominal obesity was estimated with waist circumference and lifestyle habits, by a self-reported questionnaire. Seminal parameters were analysed and collected according to the WHO guidelines (Kruger's strict criteria for seminal morphology). Results: There was a significant spousal concordance for the percentage of fat mass, leisure activities and overall nutritional quality. Accordingly, male participants displayed anthropometric and lifestyle characteristics at higher risk than Canadian men of similar age. Moreover, BMI, daily consumption of fruits & vegetables and sleeping hours in men were independently associated to the total motile sperm count. Conclusion: This is the first study to report concordance for anthropometric and lifestyle characteristics between partners of infertile couples in which the woman is obese. These characteristics in men were more adverse than in the general population and were associated with reduced sperm quality. Altogether, our results suggest that male partners of infertile couples could benefit from participating in the lifestyle intervention that is already recommended for their spouse affected by obesity. Capsule: Because partners of subfertile couples in which the woman is obese share adverse anthropometric and lifestyle characteristics, male partners should be implicated in lifestyle interventions already indicated for their spouse.